TDP-43 condensates and lipid droplets regulate the reactivity of microglia and regeneration after traumatic brain injury - Zambusi, Alessandro; Novoselc, Klara Tereza; Hutten, Saskia; Kalpazidou, Sofia; Koupourtidou, Christina; Schieweck, Rico; Aschenbroich, Sven; Silva, Lara; Yazgili, Ayse Seda; Van Bebber, Frauke; Schmid, Bettina; Moeller, Gabriel; et al. (Nature Neuroscience, 2022)
Decreasing the activation of pathology-activated microglia is crucial to prevent chronic inflammation and tissue scarring. In this study, we used a stab wound injury model in zebrafish and identified an injury-induced microglial state characterized by the accumulation of lipid droplets and TAR DNA-binding protein of 43 kDa (TDP-43)+ condensates. Granulin-mediated clearance of both lipid droplets and TDP-43+ condensates was necessary and sufficient to promote the return of microglia back to the basal state and achieve scarless regeneration. Moreover, in postmortem cortical brain tissues from patients with traumatic brain injury, the extent of microglial activation correlated with the accumulation of lipid droplets and TDP-43+ condensates. Together, our results reveal a mechanism required for restoring microglia to a nonactivated state after injury, which has potential for new therapeutic applications in humans.
CRIS-Team Scopus Importer:2023-03-08